Cloning of thermostable DNA polymerases from hyperthermophilic marine Archaea with emphasis on Thermococcus sp. 9 degrees N-7 and mutations affecting 3'-5' exonuclease activity. - Southworth, M W (1996)
Five extremely thermophilic Archaea from hydrothermal vents were isolated, and their DNA polymerases were cloned and expressed in Escherichia coli. Protein splicing elements (inteins) are present in many archaeal DNA polymerases, but only the DNA polymerase from strain GB-C contained an intein. Of the five cloned DNA polymerases, the Thermococcus sp. 9 degrees N-7 DNA polymerase was chosen for biochemical characterization. Thermococcus sp. 9 degrees N-7 DNA polymerase exhibited temperature-sensitive strand displacement activity and apparent Km values for DNA and dNTP similar to those of Thermococcus litoralis DNA polymerase. Six substitutions in the 3'-5' exonuclease motif I were constructed in an attempt to reduce the 3'-5' exonuclease activity of Thermococcus sp. 9 degrees N-7 DNA polymerase. Five mutants resulted in no detectable 3'-5' exonuclease activity, while one mutant (Glul43Asp) had <1% of wild-type activity.